Changes in physical activities patterns assessed by accelerometry after bariatric surgery: A systematic review and meta-analysis. (March 2019) - Barbosa, Carolina Gabriela Reis; Verlengia, Rozangela; Ribeiro, Anna Gabriela Silva Vilela; de Oliveira, Maria Rita Marques; Crisp, Alex Harley
Abstract: Introduction: Research into daily physical activity patterns of bariatric patients has primarily relied on self-report questionnaires. Given the importance of to moderate-to-vigorous physical activity (MVPA) as opposed to sedentary behavior for health outcomes and surgical success, more valid methods for objectively measuring physical activities are necessary. Evidence acquisition: The main question is whether bariatric surgery, weight loss, and standard care after surgery would favor the increase of physical activity level. Therefore, we conducted a systematic review and meta-analysis of retrospective studies that investigated the changes in physical activities patterns after bariatric surgery which were evaluated by accelerometry. The search was conducted in five electronic databases (PubMed, Web of Science, Google Scholar, SPORTDiscus, and Scopus) up to December 2017. The standardized mean difference (SMD) was calculated using a random effects model with a Comprehensive Meta-Analysis program. Evidence synthesis: A total of 10 studies met the inclusion criteria for the meta-analysis. Overall, the results indicated no significant changes to sedentary (SMD = −0.055; 95% confidence interval (CI) −0.149 to 0.040; p  = 0.161) and light activities per day (SMD = 0.020; 95% CI −0.095 to 0.134; p  = 0.737) post bariatric surgery. However, a positive effect was observed to MVPA per day (SMD = 0.133; 95% CI 0.040 to 0.226; p  = 0.005) and MVPA in bouts ≥10 min per week (SMD = 0.066; 95% CI 0.039 to 0.093; p  = 0.000). Conclusions: In summary, bariatric surgery per se resulted only in a trivial effect on MVPA changes after body weight loss. On the other hand, bariatric surgery did not influence sedentary behavior, indicating that bariatric patients need to be better informed about the importance of reducing sedentary activities and increasing physical activity level.